Mozambique : Public Expenditure Review, Phase 2. Sectoral Expenditures - World Bank (Washington, DC, 2013)
This is the second (and final) phase of the Public Expenditure Review (PER) for Mozambique. The first phase, initiated in 2000 and completed in 2001 , and termed the Public Expenditure Management Review (PEMR), dealt with the financial management system (see report no. 22985). It developed a large agenda for reform in all of the parts of the expenditure cycle: budgeting, execution, accounting, and auditing. Jointly with the Mozambican authorities, a final report was produced which included a time-bound action plan. This, the second phase of the PER, covers aspects of sectoral spending in four major sectors: education, health, roads and water. These sectors were selected because they account for 51 percent of government spending and for 56 percent of the civil service, and are among the six "fundamental areas of action" in the Action Plan for the Reduction of Absolute Poverty (termed PARPA, viz. Mozambique's Poverty Reduction Strategy Paper-report no. 22664). This second phase of the PER also provides an update about progress with the action plan of the first phase, the PEMR. Finally, it reports briefly on a pilot expenditure tracking exercise carried out in the specific case of health, the Expenditure Tracking and Service Delivery Survey'. The PER is a joint product of the Government and the Bank, each taking the lead in different sectors. The main objectives of the PER 2nd phase are to examine allocative efficiency and cost-effectiveness, as well as the poverty orientation of spending. Among the yardsticks used for examining the rate of service delivery are the targets set in the Government's PARPA and also the Millennium Development Goals (MDGs). The scope of the inquiry is limited. Agriculture is omitted. And concerning HIV/AIDS, research was done on the disease in general, on its macroeconomic impact, and on its impact in the educational sector, and some information was generated on its impact in the health sector. But a major study on HIV/AIDS and its impact on the health sector, and measures to be taken, is due to start during 2003. It was not possible to reflect the results of this study in the PER.